Love And Selfishness Reflected In Gary Winick‟S Letters To Juliet Movie (2010): A Psychoanalytic Approach - Pratiwi, Amellia Endah; , Drs. Abdillah Nugroho, M.Hum; , Nur Hidayat S. Pd (2013)
The research is proposed to analyze how the love and selfishness reflected in Letters to Juliet movie 2010 by Psychoanalytic Approach. There are two objectives: the first is to analyze the movie based on its structural elements and technical elements, and the second is to analyze the main character's personality using a psychoanalytic approach. This study is a qualitative study, using Gary Winnick‟s Letters to Juliet movie 2010 as of structural elements, and the secondary data. The primary data source is Letters to Juliet movie which is directed by Gary Winnick, and the secondary data are some articles, book of literary and internet related to the subject. The method of collecting data in this research is library research by watching the movie, reading some related books and articles, accessing internet, taking notes of important part, arranging, and drawing conclusion the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study shows that the movie illustrates how to love someone and selfishness attitude of the movie. One of the bad demeanors which is against love for two person is selfishness. The solution to solve the problem is try to change that behaviorism or tries to find someone else.